1990
DOI: 10.3109/15513819009064717
|View full text |Cite
|
Sign up to set email alerts
|

Combined True Thymic Hyperplasia and Lymphoid Hyperplasia in Grave's Disease

Abstract: True thymic hyperplasia (enlarged gland composed of histologically unremarkable cortical and medullary parenchyma) and lymphoid hyperplasia (medullary lymphoid follicles in the clinical setting of autoimmunity) usually develop as independent pathologic processes. We reviewed the clinical features and gross and microscopic pathology of 2 hyperthyroid patients with features of both thymic hyperplasia and lymphoid hyperplasia. The diagnosis of thymic hyperplasia was supported by thymic weights greater than two st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…). Human patients with hyperthyroidism experience both true thymic hyperplasia caused by increased thyroxine, and lymphoid follicular hyperplasia attributed to the autoimmune disorder underlying the syndrome (Judd and Bueso‐Ramos ). The case presented in this report developed true thymic hyperplasia based on the histopathology and history of chronic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…). Human patients with hyperthyroidism experience both true thymic hyperplasia caused by increased thyroxine, and lymphoid follicular hyperplasia attributed to the autoimmune disorder underlying the syndrome (Judd and Bueso‐Ramos ). The case presented in this report developed true thymic hyperplasia based on the histopathology and history of chronic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, true thymic hyperplasia, which is usually detected by chest X-ray or CT, is also known to complicate Graves disease [ 4 9 , 16 ]. Judd et al [ 17 ] reported that true and lymphoid thymic hyperplasia can be combined in Graves disease. In our study, thymic biopsy was not performed in any patient.…”
Section: Discussionmentioning
confidence: 99%
“…Este estudo constatou um aumento das regiões cortical e medular da glandula pré-tratamento e a regressão do tecido cortical com manutenção do aumento da região medular após tratamento prolongado com ATS 18 .…”
Section: Discussionunclassified